1999
DOI: 10.1021/ja991102w
|View full text |Cite
|
Sign up to set email alerts
|

Biosynthetic Studies on the α-Glucosidase Inhibitor Acarbose in Actinoplanes sp.:  2-epi-5-epi-Valiolone Is the Direct Precursor of the Valienamine Moiety

Abstract: The biosynthetic pathway leading to the mC7N cyclitol (valienamine) moiety of acarbose (1) in Actinoplanes sp. strain SN 223/29 has been studied using 3H-, 2H-, and 13C-labeled cyclitols. These precursors were synthesized from d-glucose or d-mannose as starting materials. The feeding experiments demonstrated that cyclitols having the same stereochemistry at C-2 as the valienamine moiety of acarbose; i.e., valienone, valienamine, valiolone, valiolamine, and 1-epi-valienol, were not incorporated and thus are not… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

5
71
0

Year Published

2000
2000
2021
2021

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 64 publications
(76 citation statements)
references
References 29 publications
5
71
0
Order By: Relevance
“…This conversion step was unexpected because it seemed more likely that either dehydration at positions 5 and 6 or reduction of the keto group at position 1 of the cyclitol came first. The fact that 2-epi-5-epi-valiolone is first phosphorylated and only thereafter further modified by other biosynthetic enzymes such as AcbO is in good accordance with all feeding experiments with whole cells that have been performed so far (8). In these studies, 2-epi-5-epi-valiolone was the only extracellularly provided C 7 -cyclitol that was incorporated into acarbose.…”
Section: Fig 5 Tlc Analyses Of Acbm and Acbo Assays Extracts Fromsupporting
confidence: 83%
See 4 more Smart Citations
“…This conversion step was unexpected because it seemed more likely that either dehydration at positions 5 and 6 or reduction of the keto group at position 1 of the cyclitol came first. The fact that 2-epi-5-epi-valiolone is first phosphorylated and only thereafter further modified by other biosynthetic enzymes such as AcbO is in good accordance with all feeding experiments with whole cells that have been performed so far (8). In these studies, 2-epi-5-epi-valiolone was the only extracellularly provided C 7 -cyclitol that was incorporated into acarbose.…”
Section: Fig 5 Tlc Analyses Of Acbm and Acbo Assays Extracts Fromsupporting
confidence: 83%
“…Earlier work has demonstrated that 2-epi-5-epi-valiolone is the precursor of the C 7 -cyclitol unit of the acarviosyl moiety of acarbose (5,8). The expectation was that a series of enzymecatalyzed steps involving dehydration, reduction, and epimerization converted this precursor to valienol (or valienamine) before its incorporation into the pseudodisaccharide acarviosine.…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations